2013
DOI: 10.1515/gps-2013-0076
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticle-supported organocatalysis

Abstract: Magnetic nanoparticle (MNP)-supported catalysis is a new method to facilitate catalyst separation and reuse. This technique has recently been introduced for organocatalysis. MNP-supported organocatalysts have been evaluated for their activity, selectivity, and recyclability in a range of chemical transformations, especially for asymmetric synthesis. The synthesis and application of Fe 3 O 4 MNP-supported organocatalysis are highlighted in this short review article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[24][25][26] In the catalysis arena, a sustained effort has been made to develop eco-friendly strategies to generate these nanomaterials via pathways that use benign reagents. 27 Recently, several reports have shown that many reactions can be conducted by using immobilized MNP catalytic systems, [27][28][29][30][31][32][33] with the advantages of the heterogeneous catalysts mentioned above and applicable in asymmetric synthesis, by the use of chiral-ligand-modified or organocatalyst-bonded MNPs as asymmetric catalysts. However, these papers mention asymmetric reaction together with many others, so a critical review focused on this topic is still lacking.…”
Section: Renato Dalpozzomentioning
confidence: 99%
“…[24][25][26] In the catalysis arena, a sustained effort has been made to develop eco-friendly strategies to generate these nanomaterials via pathways that use benign reagents. 27 Recently, several reports have shown that many reactions can be conducted by using immobilized MNP catalytic systems, [27][28][29][30][31][32][33] with the advantages of the heterogeneous catalysts mentioned above and applicable in asymmetric synthesis, by the use of chiral-ligand-modified or organocatalyst-bonded MNPs as asymmetric catalysts. However, these papers mention asymmetric reaction together with many others, so a critical review focused on this topic is still lacking.…”
Section: Renato Dalpozzomentioning
confidence: 99%
“…Nanoparticles are widely used for organic synthesis. 1 Due to their nanometer size and magnetic properties, they are effective as homogeneous-like systems that integrate the advantages of high dispersion, high reactivity, and simple separation. 2 Magnetic nanoparticles (MNPs) have been well employed to immobilize organic ligands, organocatalysts, and biocatalysts through absorption or formation of covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…2 Magnetic nanoparticles (MNPs) have been well employed to immobilize organic ligands, organocatalysts, and biocatalysts through absorption or formation of covalent bonds. 1 Moreover, MNPs such as iron oxide have a high surface area, superior thermal and chemical stability, surface modication ability, ease of synthesis, and low toxicity and cost. 3 Researchers' attention has been drawn to immobilization of amino acids on the surface of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%